Recovery of Li, Mn, and Fe from LiFePO4/LiMn2O4 mixed waste lithium-ion battery cathode materials - Wang, Yahui; Wu, Jijun; Hu, Guochen; Ma, Wenhui (Journal of Mining and Metallurgy, Section B: Metallurgy, 2023)
The recovery of metals from used lithium-ion battery cathode materials is of both environmental and economic importance. In this study, acid leaching stepwise precipitation was used to separate and recover lithium, iron, and manganese from the mixed cathode material LiFePO4/LiMn2O4. The thermodynamic characteristics of lithium, iron, and manganese metal phases, especially the stability region, were analyzed by Eh-pH diagrams. The sulfuric acid and hydrogen peroxide leaching system released Fe3+, Mn2+, and Li+ ions from the cathode material. Fe3+ in the leaching solution was precipitated as Fe(OH)3 and finally recovered as Fe2O3 after calcination. Mn2+ in the leaching solution was recovered as MnCO3. The remaining Li+-rich solution was evaporated and crystallized into Li2CO3. The purity of the recycled products MnCO3 and Li2CO3 met the standard of cathode materials for lithium-ion batteries. XRD and XPS analysis showed that the main phase in the leaching residue was FePO4. This process can be used to separate and recover metals from mixed waste lithium-ion battery cathode materials, and it also provides raw materials for the preparation of lithium-ion battery cathode materials.